Revealing the deeper forces impacting women’s lives after COVID-19 - International Potato Center (International Potato Center, 2022)
As the world emerges from the pandemic, agricultural researchers have begun training their lenses to understand how COVID-19 has affected the lives of women in agri-food systems in developing countries. To inform development initiatives and investments, having a proper and specific understanding of women’s experience is paramount. However, many feminist researchers express concern that the methods used in these investigations often miss the nuance if they focus heavily on capital or production and ignore reproduction or the specific ways that women experience changes in agriculture and their livelihoods due to the impacts of COVID-19. Against this backdrop, the CGIAR GENDER platform organized a webinar to share results and learning from exciting new research projects which focused on these important questions about impact and methods.